Subglobal climate agreements and energy-intensive activities: An evaluation of carbon leakage in the copper industry - Bruno Lanz; Thomas F. Rutherford; John E. Tilton (ETH Zurich, CER-ETH - Center of Economic Research, 2013)
Subglobal climate policies induce changes in international competitiveness and favor a relocation of carbon-emitting activities to non-abating regions. In this paper, we evaluate the potential for CO2 abatement and the emissions `leakage' effect in the copper industry, a prominent energy-intensive trade-exposed sector. We formulate a plant-level spatial equilibrium model for copper commodities in which parameters describing the behavioral response of agents are calibrated to econometric estimates of price elasticities. We find producers and consumers to be price inelastic even in the long-run, making the copper industry unresponsive to climate policies. Monte Carlo simulations with our model based on statistical uncertainty on elasticity estimates suggest that around 30% of emissions reductions in industrialized countries would be compensated by an increase of emissions in non-abating countries.
Keywords: F18; F55; H23; Q54; Q58; 330; Carbon leakage; Pollution haven effect; Climate policy; International environmental agreements; International trade; Copper industry; Umweltabkommen; Treibhausgas-Emissionen; Umweltabgabe; Umweltstandard; Branchenentwicklung; Kupferindustrie; Monte-Carlo-Simulation; Welt